The effectiveness of religious module in improving psyco-spiritual health for women inmates in prison - Mohamad Jodi K.H.; Bin Mohamad M.A.; Mohd Radzi W.; Che Seman A.; Abd Rahman N.; Fairuz Ramlan S.; Johari F.; Nurhanisah Senin (2024)
Indexed by Scopus